2003
DOI: 10.1385/mo:20:1:25
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metastasis at the Time of Initial Diagnosis of Lung Cancer

Abstract: In order to evaluate clinicopathological features associated with liver metastases from lung cancer, we reviewed our experience of lung cancer patients seen in our division. Of the 1073 lung cancer patients diagnosed between October 1976 and May 2002, 62 (5.8%) patients had liver metastasis. The incidence of liver metastasis was 17.5% in small-cell lung cancer (SCLC) patients, whereas the incidence in non-small-cell lung cancer patients was 3.8%. Of the 62 patients, 17 had sole liver metastasis, and the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…Second, liver metastasis was an unfavorable prognostic factor in our study, which was consistent with previously reported results (3,5). Liver metastatic lesions are rarely associated with severe symptoms, although the majority of NSCLC patients had multiple nodules morphologically (17). It is well known that the majority of NSCLC patients with liver metastasis do not respond well to chemotherapy (18,19).…”
Section: Variablessupporting
confidence: 91%
“…Second, liver metastasis was an unfavorable prognostic factor in our study, which was consistent with previously reported results (3,5). Liver metastatic lesions are rarely associated with severe symptoms, although the majority of NSCLC patients had multiple nodules morphologically (17). It is well known that the majority of NSCLC patients with liver metastasis do not respond well to chemotherapy (18,19).…”
Section: Variablessupporting
confidence: 91%
“…The discontinuation of chemotherapy due to the deterioration of ADL in these patients has a certain correlation with poor survival. With regard to liver metastasis, the majority of SCLC patients had multiple nodules in our previous study (16). SCLC may cause biliary tract obstruction by metastasizing to lymph nodes in the porta hepatis or hepatic parenchyma (17,18).…”
Section: Discussionmentioning
confidence: 88%
“…In addition to harboring primary tumors, the liver is often the target organ for metastatic lesions from colon (2), breast (3), or lung cancers (4). Unfortunately, treatment failure is frequent and results in high recurrence rates with short survival times (5-7).…”
Section: Introductionmentioning
confidence: 99%